Political and Health Influences on Demand for Indonesian Tourism - Prayitno, Andaru Rachmaning Dias; Haryanto, Tri; Auwalin, Ilmiawan (Department of Development Economics, Universitas Sriwijaya, 2024)
This study examines the impact of income, exchange rates, political conditions, and health factors on Indonesian tourism demand from 2010 to 2019, using multiple and panel regression analyses with data from Statistics Indonesia (BPS), the World Bank, the Central Bank of Indonesia (BI), and the World Health Organization (WHO). The findings indicate that the income of tourists from China, Australia, Timor Leste, and other analyzed countries positively affects tourism demand, while income from Malaysia and Singapore shows no significant effect. Exchange rates positively influence tourists from Malaysia, Singapore, Australia, Timor Leste, and other analyzed countries, but have no significant effect on Chinese tourists. Political conditions negatively impact Australian tourists, positively influence tourists from other analyzed countries, and have no significant effect on tourists from Malaysia, China, Singapore, and Timor Leste. Health factors negatively affect tourists, while having no significant effect on tourists from Singapore and Australia. The study recommends that the government enhance tourism supply to boost demand, with a focus on improving environmental sustainability, health, tourism service infrastructure, and security and safety. Additionally, there is a need for standardized governance rules to better manage the impacts of outbreaks or disasters on the tourism sector.